2017
DOI: 10.1590/1983-21252017v30n303rc
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Cowpea Under Water Stress and Rewatering in No-Tillage and Conventional Tillage Systems

Abstract: -The goal of this work was to evaluate the physiological responses of cowpea under water stress and rehydration in conventional and no-tillage systems. We evaluated two crop systems (conventional and no tillage) and three water conditions (no stress, moderate stress and severe stress). The following were determined: leaf area, total dry matter, photosynthetic rate, stomatal conductance, transpiration rate, internal CO 2 concentration and leaf water potential. Water stress affected all variables evaluated, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
0
21
0
8
Order By: Relevance
“…Some authors observed, however, that cowpea can preserve leaf water potential (Freitas et al, 2017) and relative water content (Anyia & Herzog, 2004) even under cumulative water deficit conditions, a characteristic also observed by Guimarães et al (2006) for common beans, suggesting that the crop acts as a conservative species by prioritizing the maintenance of its water status rather than its photosynthetic activity, corroborating the reduction found in its WUE in the presence of water deficit.…”
Section: Resultsmentioning
confidence: 75%
“…Some authors observed, however, that cowpea can preserve leaf water potential (Freitas et al, 2017) and relative water content (Anyia & Herzog, 2004) even under cumulative water deficit conditions, a characteristic also observed by Guimarães et al (2006) for common beans, suggesting that the crop acts as a conservative species by prioritizing the maintenance of its water status rather than its photosynthetic activity, corroborating the reduction found in its WUE in the presence of water deficit.…”
Section: Resultsmentioning
confidence: 75%
“…However, due to the irregularity of rainfall in these regions, it is common to experience long periods without rain during the crop cycle. In this case, plant survival and crop yield will depend on strategies such as water conservation or tolerance to drought (Freitas et al, 2017). Typically, new cultivars are obtained by selection during harvest and according to their components in specific environments without evaluating the effects of drought in different growth and development stages.…”
Section: Introductionmentioning
confidence: 99%
“…), as it is moderately resistant to drought, can be grown under different edaphoclimatic conditions. That vegetable is widely grown and consumed globally, being used as the main source of protein [1]. For the 2012-2014 period, the average global yield was 7.32 million tons [2].…”
Section: Introductionmentioning
confidence: 99%